Development of a Culturally Responsive Teaching and Learning Model Based on the Merdekan Curriculum at Madrasah Ibtidaiyah - Nashran Azizan; Lubis, Maulana Arafat (Universitas Islam Lamongan, 2025)
Learning models play a vital role in maximizing educational outcomes. Therefore, it is essential for teachers to thoughtfully select and implement instructional models that align with effective teaching practices. However, the success of any model also relies heavily on the presence of a solid support system, such as well-prepared teaching materials and student books, which help make learning more meaningful and engaging. The development of the Culturally Responsive Teaching (CRT) model stems from the necessity to create educational experiences that are not only academically sound but also culturally appropriate, particularly in diverse classroom settings. By embedding local cultural values into lessons, CRT aims to enhance student engagement, reinforce cultural identity, and promote civic understanding. This study aimed to develop a CRT model for use in Pancasila Education that is valid, practical, and effective in improving the learning outcomes of elementary school students in Padangsidimpuan City. The research employed a Research and Development (R&D) approach, using the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. The study was conducted at MIN 1 Padangsidimpuan, involving fourth-grade students as the sample. Data collection techniques included observation, testing, questionnaires, interviews, and documentation. Data analysis was performed both quantitatively, using SPSS software, and qualitatively. The findings indicate that the CRT model and its supporting materials are highly valid and practical, making them easy for teachers and students to use. Furthermore, the model was found to be very effective based on students' learning outcomes across two test phases.